Dinamika Etnis Dalam Proses Politik Lokal Daerah (Studi Kasus Pemilihan Bupati dan Wakil Bupati Kabupaten Toli-Toli Provinsi Sulawesi Tengah Tahun 2010) - Kahar, Abdul; Qodir, Zuly (Journal of Governance and Public Policy, 2015)
This study aims to explain the Bugis ethnic considerations in the Legislative Elections of 2014 in Toli-Toli. This studyused qualitative methods (qualitative research) and in-depth interviews (deep interview) to the resource persons whoare considered able to answer related to problems that intended by the author. based on the data captured, it can beconcluded that the instrumentation of local identities such as ethnicity plays an important role in determining thecandidates to be selected. It has become a phenomenon of the present era, but in this study, the author presents dataon the ethnic Bugis ethnic immigrants in Toli-Toli, but the procession of legislative elections, ethnic Bugis is able toshow its existence. On behalf of the social and economic similarities, the election of the candidate of the group into themajor. Human Resources should be the guarantee of someone who was worthy to be their representative in thelegislature become a factor not taken into account by people of ethnic Bugis ethnic krena only see the similarity ofidentity. As for the recommendation of the author that the local government as the supreme authority needs tosocialize through social activities which contains items essential to living together in the frame of unity without distinguishingone another, as well as community leaders of ethnic Bugis as people in by society should regardless ofkeberpihakannya, in that it has always adhered to a single diversity diversity.